EKONOMI DIGITAL ‘ADVERTISING CINEMATIC’ OPPO CINEFINDERS SIKLUS KARYA GARIN NUGROHO - Ahmad Toni; Jauharotul Maknunah (Jurnal Imagine, 2023)
This research is a cinematic study of film technique and the meaning contained in each cinematic element in the film Siklus by Garin Nugroho produced by Oppo Indonesia using the Oppo Find X3 Pro 5G smartphone camera. The research method used is a cinematic study, this method is used to interpret a number of cinema element. The results show: the film ‘Oppo cinema finders’ with the Oppo Find X3 Pro 5G smartphone camera device whose camera specifications are to offer 1 billion colors with 12 GB RAM and file storge capacity up to 250 GB and image resolution reaching 3216 x 1440 QHD+. The aesthetic condition of the film the describes space and time of life, nature and the movement of the time combined with dynamic, slow storyline narrative, curiosity and able to invite the audience into the space and time contained in the film setting. And modern and classical artistic arrangements. The dramatic effect embodied in cinematic capture in this film is little used as the main ingredient, this is because the natural narrative system between the past and the present can be integrated into one imaginative event. The natural nature of the images depicting the cinematics in this film shows the nuances of the reality of marginalized life from traditional culture and the condition of the area (city) which is dominated by old buildings (history) but in an imaginary reality. This film director ability to manage the framing system makes the standard smartphone camera patterns and other production element sepak of excellence and good production capabilities.